New challenges for South African development and training -- linkages to empirical research. - Jinabhiai DC (Public Personnel Management)
With the introduction in South Africa of the Skills Development Act (1998) and the Skills Development Levies Act (1999) respectively, employer organizations are obliged to set aside a portion of their annual payroll for the internal training and development of their workforce. The function of the statutory National Skills Authority (NSA) is to implement the skills development strategy, monitor its performance and report the progress made by the Sector Education and Training Authorities (SETAs). In the South African context, training and development has only recently received attention as a means of addressing critical personnel development initiatives. The focus is now shifting towards fast tracking skills development, which is being integrated into the overall business plan of organizations. Strategies need to be initiated to harness knowledge workers as competitive resources for the new global economy and for world-class competitiveness. This article accentuates the importance of the skills development strategy and offers a systems approach to skills development for organizations. It also highlights some empirical research and its linkages to the emerging challenges of the skills development strategy in South Africa. The article concludes with implications for skills development and training and maps the way for future research.